Faktor Penghambat Dan Pendukung Implementasi Kebijakan Pengembangan Pariwisata Kota Cirebon - Cecep Wahyu Hoerudin; Siti Alia; Maya Sukmanita (Department of Public Administration, 2018)
The research carried out aims to find out the extent of the implementation of Law Number 10 Year 2009 concerning Tourism, whether this policy has been properly implemented or not and to find out how the efforts made by policy providers (the Government) to advance the tourism potential in the city of Cirebon, especially Kejawan Beach. The research method used in this study is a qualitative method with a descriptive design because in this study, data collection through observation and interviews is obtained directly down to the field, therefore the techniques used were Purposive Sampling and Accidental techniques. The results of the study show that the implementation of Law Number 10 of 2009 has not gone well and there is still a lack of tourist attraction to visit the coast due to the lack of government attention to the shore beaches, and the lack of complete infrastructure and governance that has not been maximized in accordance with Law Number 10 of 2009.